Assessment on trophic status of Nha Trang bay using environmental and phytoplankton based indices - Ngoc Duyen, Huynh Thi; Mai Anh, Nguyen Thi; Thoi, Nguyen Chi; Le Van, Tran Thi; Luom, Phan Tan; Lam, Nguyen Ngoc; Hai, Doan Nhu (Academia Journal of Biology, 2015)
Ten year data of environment and phytoplankton community structure were used to calculate trophic status indices of Nha Trang Bay. The two indicating groups, environmental and phytoplankton based indices, were different and varied in time. Both TRIX (4.3-5.9) and TSI (28.5-53.1) indices indicated Nha Trang Bay was in oligotrophic to mesotrophic status. However, trophic diatoms index, TDI (1.4-5.0) indicated high frequency of mesotrophic and eutrophic status of the waters. Ratios of centric to pennate diatoms (C/P, both in species number and in abundance) frequently indicated eutrophic status (>2.0) of the waters. Correlation matrix showed possitive relationships amongst environmental and phytoplankton based indices. The present study suggested that phytoplankton ratios, Dia/Dino-N and C/P-N indices, are applicable in assessing trophic status of coastal waters. The TDI index, however, is needed for further studies to be applicable for coastal waters.